Analysis Of Children’s Interest In Gross Motor Skills Through Audio Visual Based Gymnastics Activities - Khotimah, Khusnul; Asmawulan, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This ponder points to analyze children's intrigued in net engine skills. Methodology: Investigate strategy utilized could be a sort of subjective inquire about that centers on perception. The subjects of this study were teachers or instructors, students in the age group of 5-6 years at Kindergarten Bintang Al Qur'an Tulung.. Results: Results of this study show that healthy Friday gymnastics activities carried out using audio visual media can attract interest in gross motor aspect skills in early childhood.. Applications/Originality/Value: This study can be applied as a reference for teachers and parents to design more engaging gross motor activities by integrating audiovisual media to maintain and increase young children’s interest and participation during physical exercises.